2014
DOI: 10.1021/cm501438j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Conductive Properties of Gold Nanoparticles Protected by Partially Bicyclo[2.2.2]octene-Annelated and Methylthio End-Capped Oligothiophene Thiolates

Abstract: Gold-nanoparticles (AuNPs) protected by thiolates of methylthio end-capped terthiophene 1a and quaterthiophene 2a partially annelated with bicyclo[2.2.2]octene (BCO) unit(s) were designed and synthesized. AuNP covered with nonannelated terthiophene 3a was also synthesized for comparison. The formation of the AuNPs was confirmed by absorption spectra and transmission electron microscopy (TEM) measurements. The electric conductivities of AuNP-1a − and AuNP-3a − films were moderate (∼10 −3 S cm −1 ) due to conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Considering the intimate relationship between electronic communication and electronic conduction through molecular wires, the conjugated oligomer radical cation π‐dimers are expected to be a component of redox‐responsible conductive supramolecular systems. For example, a new switching device based on the molecular wire properties of π‐dimers may be developed from gold nanoparticles covered with the conjugated oligomers . In addition to the expected conductive properties, the strong exchange interactions in the π‐dimer moiety may be applicable to spintronics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the intimate relationship between electronic communication and electronic conduction through molecular wires, the conjugated oligomer radical cation π‐dimers are expected to be a component of redox‐responsible conductive supramolecular systems. For example, a new switching device based on the molecular wire properties of π‐dimers may be developed from gold nanoparticles covered with the conjugated oligomers . In addition to the expected conductive properties, the strong exchange interactions in the π‐dimer moiety may be applicable to spintronics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a new switching device based on the molecular wire properties of p-dimers may be developed from gold nanoparticles covered with the conjugated oligomers. [71] In addition to the expected conductive properties, the strong exchange interactions in the p-dimer moiety may be applicable to spintronics.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] In addition, it has recently been demonstrated that controlled p-dimer formation induces the assembly of supramolecular structures, [28,29] the switching of molecular motions,a nd the switchingo fm olecular-level electric conduction through p-dimers. [30] Therefore, to increase our fundamental understanding and expand the range of practical applications, [31] there has been growing interesti ne xtracting the important structuralf actors that determine p-dimer formation.I n this context, we need as pecific molecular design that fulfills an umber of research purposes:o ligothiophenes should be developed that can control the intermolecular interactions and concomitantlym aintain the intrinsic electronic properties and effective conjugation of pristine oligothiophenes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, oligothiophenes and polythiophenes bearing bulky substituents that prevent the formation of face‐to‐face π‐dimers have been utilized to elucidate the properties of single π‐conjugated chains in the absence of intermolecular interactions 23–27. In addition, it has recently been demonstrated that controlled π‐dimer formation induces the assembly of supramolecular structures,28, 29 the switching of molecular motions, and the switching of molecular‐level electric conduction through π‐dimers 30. Therefore, to increase our fundamental understanding and expand the range of practical applications,31 there has been growing interest in extracting the important structural factors that determine π‐dimer formation.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of 1 2+ and 2 2+ , the VT measurements showed quite similar changes upon lowering the temperature as shown in Figure A,B, indicating that the similar π‐dimerization took place. These results suggested that supramolecular wires based on π‐dimerization between dication diradicaloids in a slipped stack manner were formed at the lower temperatures. Unfortunately, no farther evidence could not be obtained for the formation of supramolecular polymer, partly because the π‐dimerization was observed only at low temperatures in solution phase.…”
Section: Resultsmentioning
confidence: 99%